GPR4 Knockout Improves the Neurotoxin-Induced, Caspase-Dependent Mitochondrial Apoptosis of the Dopaminergic Neuronal Cell - Haque, Md Ezazul (Int J Mol Sci, 2020)
In Parkinson’s disease, mitochondrial oxidative stress-mediated apoptosis is a major cause of dopaminergic neuronal loss in the substantia nigra (SN). G protein-coupled receptor 4 (GPR4), previously recognised as an orphan G protein coupled-receptor (GPCR), has recently been claimed as a member of the group of proton-activated GPCRs. Its activity in neuronal apoptosis, however, remains undefined. In this study, we investigated the role of GPR4 in the 1-methyl-4-phenylpyridinium ion (MPP(+)) and hydrogen peroxide (H(2)O(2))-treated apoptotic cell death of stably GPR4-overexpressing and stably GPR4-knockout human neuroblastoma SH-SY5Y cells. In GPR4-OE cells, MPP(+) and H(2)O(2) were found to significantly increase the expression levels of both mRNA and proteins of the pro-apoptotic Bcl-2-associated X protein (Bax) genes, while they decreased the anti-apoptotic B-cell lymphoma 2 (Bcl-2) genes. In addition, MPP(+) treatment activated Caspase-3, leading to the cleavage of poly (ADP-ribose) polymerase (PARP) and decreasing the mitochondrial membrane potential (ΔΨm) in GPR4-OE cells. In contrast, H(2)O(2) treatment significantly increased the intracellular calcium ions (Ca(2+)) and reactive oxygen species (ROS) in GPR4-OE cells. Further, chemical inhibition by NE52-QQ57, a selective antagonist of GPR4, and knockout of GPR4 by clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 decreased the Bax/Bcl-2 ratio and ROS generation, and stabilised the ΔΨm, thus protecting the SH-SY5Y cells from MPP(+)- or H(2)O(2)-induced apoptotic cell death. Moreover, the knockout of GPR4 decreased the proteolytic degradation of phosphatidylinositol biphosphate (PIP(2)) and subsequent release of the endoplasmic reticulum (ER)-stored Ca(2+) in the cytosol. Our results suggest that the pharmacological inhibition or genetic deletion of GPR4 improves the neurotoxin-induced caspase-dependent mitochondrial apoptotic pathway, possibly through the modulation of PIP(2) degradation-mediated calcium signalling. Therefore, GPR4 presents a potential therapeutic target for neurodegenerative disorders such as Parkinson’s disease.